The Emerald handbook of quantum storytelling consulting - Boje, David M.; Sanchez, Mabel (Emerald Publishing Limited, 2018)
There is a paradigm shift happening in storytelling consulting. The oldone-story-fits-all consulting paradigm - helping companies to brand their founding story, do elevator pitches, and deliver stump speeches - is giving way to quantum storytelling consulting. The quantum age has moved away from a mechanist, Newtonian, simple-cause-and-effect understanding of reality and life, and storytelling consulting is now about an ensemble of stories rather than a single pitch. It's about developing the spaces for storytelling processes; it's about the times when storytelling is emerging; and it's about the kinds of 'mattering' or material agency that the storytelling has. In the quantum age, space, time, and mattering have no separation; instead, 'spacetime mattering' storytelling emerges, self-organizes, and creates change management. It is no longer thecase that one narrative fits all. Rather, it is the interplay of many living stories that create the complex forces of change within organizations. 'The EmeraldHandbook of Quantum Storytelling Consulting' collects the findings of quantum storytelling researchers and consultants to develop a practical understanding of quantum storytelling consulting by sharing case examples, describing how to enact specific practices, and outlining how to conduct research into the impact and consequences of quantum thinking.
Prelims -- Introduction -- Section I Quantum storytelling consulting -- Quantum storytelling consulting, ensemble leadership theory, and world ecology -- The break: worklife balance and leadership Anno 2016: reconfiguring contemporary leadership through the 2,400-year-old coaching concept of protreptic, walking, and material storytelling -- Improv theater for leadership pedagogy -- Sociomaterial fractals in a quantum storytelling frame -- Storytelling on consciousness-based view of organizing -- Section II Applications to fields of study -- Tolerance for critical thinking via entrepreneurial storytelling -- Revealing antenarratives in the autism of quantum storytelling -- Sande leadership: sustainable education and professional development -- Testimonios: conduits for communication and preparation -- Quantum storytelling network analysis of supply chain management: a case study -- Reading behind the scene of public stories: quantum storytelling triangulation -- The fulfillment of Panda Express's mission statement in its macro and micro storytelling -- Entangling organizations:intra-active ways of reworking the organizational scenography for the processes of becoming of the changed relationalities of (dis)ability -- autoethnography and sensemaking: a Persian management scholar -- Bike-sharing from a quantum storytelling perspective -- Section III Research methods for quantum storytelling consulting -- Organizational-world creating: being-in-becoming. a quantum relational process philosophy -- Ten story metrics for organizations -- Mapping quantum storytelling fractal patterns before and beneath triple bottom lines -- Index.
Includes index.
Print version record
Keywords: Organizational behavior; Storytelling; Organizational change; Business & Economics -- Organizational Behavior; Organizational theory & behaviour